2019
DOI: 10.1002/sctm.18-0263
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Functional Characterization of Müller Glia Isolated from Induced Pluripotent Stem Cell-Derived Retinal Organoids: Improvement of Retinal Ganglion Cell Function upon Transplantation

Abstract: Glaucoma is one of the leading causes of blindness, and there is an ongoing need for new therapies. Recent studies indicate that cell transplantation using Müller glia may be beneficial, but there is a need for novel sources of cells to provide therapeutic benefit. In this study, we have isolated Müller glia from retinal organoids formed by human induced pluripotent stem cells (hiPSCs) in vitro and have shown their ability to partially restore visual function in rats depleted of retinal ganglion cells by NMDA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 24 publications
1
55
0
2
Order By: Relevance
“…Intravitreal injection of Müller glia with stem cell characteristics into experimental models of RGC and photoreceptor cell damage has resulted in partial recovery of retinal function, and in the absence of retinal cell integration, this effect can only be attributed to the neuroprotective functions of these cells. [98][99][100] Cellular approaches utilizing Müller glia may have the potential to bypass many of the current issues of neurotrophin delivery, with cells offering the advantage of being able to deliver a wide range of neuroprotective factors into the retinal microenvironment (summarized in Figure 2). They are naturally homeostatic and responsive to change, and their continuous production of these factors may potentially prolong the bio-availability of neuroprotectant molecules within the damaged retina.…”
Section: Potential Of Müller Glia As a Vehicle To Deliver Neuroprotecmentioning
confidence: 99%
“…Intravitreal injection of Müller glia with stem cell characteristics into experimental models of RGC and photoreceptor cell damage has resulted in partial recovery of retinal function, and in the absence of retinal cell integration, this effect can only be attributed to the neuroprotective functions of these cells. [98][99][100] Cellular approaches utilizing Müller glia may have the potential to bypass many of the current issues of neurotrophin delivery, with cells offering the advantage of being able to deliver a wide range of neuroprotective factors into the retinal microenvironment (summarized in Figure 2). They are naturally homeostatic and responsive to change, and their continuous production of these factors may potentially prolong the bio-availability of neuroprotectant molecules within the damaged retina.…”
Section: Potential Of Müller Glia As a Vehicle To Deliver Neuroprotecmentioning
confidence: 99%
“…Researchers from the laboratories of G. Astrid Limb and Karen Eastlake (UCL Institute of Ophthalmology, Moorfields Eye Hospital, London, UK) previously discovered that the transplantation of retinal ganglion cells differentiated from a human Müller glia cell line in a rat model of glaucoma‐like damage provided encouraging therapeutic outcomes . Now, the team returns with a new Stem Cells Translational Medicine article in which they report on the therapeutic outcomes of the transplantation of Müller glia isolated from human (h)iPSC‐derived retinal organoids . Eastlake and colleagues first confirmed the identity and purity of Müller glia isolated from hiPSC‐derived retinal organoids via gene/protein analysis of well‐known Müller glia markers.…”
Section: Featured Articlesmentioning
confidence: 99%
“…To move retinal regenerative therapies forward, we must identify a suitable source for Müller glia; can we derive these highly useful cells from hPSCs? In our second Featured Article from Stem Cells Translational Medicine , Eastlake et al establish that the intravitreal transplantation of iPSC‐derived Müller glia into an experimental rat model of glaucoma partially restores visual function, thereby suggesting their potential application in human retinal therapies . In a Related Article from Stem Cells , Xu et al demonstrated how a sphere‐induced cell rejuvenation and reprogramming protocol returned lost function to human and swine Müller glia, which may extend their application in basic research and therapeutic approaches .…”
mentioning
confidence: 99%
“…Stem‐like Müller glia isolated from the adult cadaveric human retina have shown promise in the restoration of visual function in rodent and feline models of retinal disease; however, the source of these highly utile cells present problems to clinical translation due to the risk of disease transmission caused by prions and non‐identified pathogens as well as histocompatibility issues. To solve this vexing problem, researchers led by Karen Eastlake and G. A. Limb (Moorfields Eye Hospital, London, UK) sought to isolate Müller glia from retinal organoids generated from human iPSCs and evaluate their ability to restore visual function in a rat model of glaucoma (NMDA‐mediated depletion of retinal ganglion cells), a major cause of blindness . Interestingly, the authors of this STEM CELLS Translational Medicine article discovered that retinal organoid‐derived Müller glia failed to integrate into the retina following intravitreal transplantation even though they observed partial restoration of retinal ganglion cell function.…”
Section: Related Articlesmentioning
confidence: 99%
“…In our second Featured Article published in STEM CELLS this month, Chichagova et al establish the need for careful consideration when selecting a protocol for retinal organoid formation by highlighting the dependence of overall efficiency on the signaling pathways modulated after their exploration of BMP4‐ or insulin‐like growth factor 1 (IGF1)‐dependent protocols . In a Related Article published in STEM CELLS Translational Medicine , Eastlake et al highlighted the therapeutic potential of transplanting Müller glia isolated from iPSC‐derived retinal organoids as a means to restore lost visual function in a mouse model of retinal degeneration …”
mentioning
confidence: 99%